Jordan-Dedekind condition in hyperlattices. Issue 4 (19th May 2018) - Bideshki, Mohsen Amiri; Saeid, Arsham Borumand
Abstract: This paper aimed to study distributivity and Jordan-Dedekind condition in hyperlattices. Hyperlattice L satisfies the Jordan-Dedekind condition if all maximal chains between the same end points have the same (finite) length. In finite modular hyperlattices, the Jordan-Dedekind condition was shown to be held. Finally, some results related to distributive hyperlattices were presented.